The gender gap in mortality: How much is explained by behavior? - Johannes Schünemann; Holger Strulik; Timo Trimborn (Vienna University of Technology, Institute of Statistics and Mathematical Methods in Economics, Research Group Economics, 2016)
In developed countries, women are expected to live about 4-5 years longer than men. In this paper we develop a novel approach in order to gauge to what extent gender differences in longevity can be attributed to gender-specific preferences and health behavior. For that purpose we set up a physiologically founded model of health deficit accumulation and calibrate it using recent insights from gerontology. From fitting life cycle health expenditure and life expectancy we obtain estimates of the gender-specific preference parameters. We then perform the counterfactual experiment of endowing women with the preferences of men. In our benchmark scenario this reduces the gender gap in life expectancy from 4.6 to 1.4 years. When we add gender-specific preferences for unhealthy consumption, the model can motivate up to 88 percent of the gender gap. Our theory offers also an economic explanation for why the gender gap declines with rising income.
Keywords: D91; J17; J26; I12; 330; health; aging; longevity; gender-specific preferences; unhealthy behavior